The Transforming the Household Economy Through Home Industry: (Analysis of the Social and Economic Impact of the Ijuk Argo Jaya Home Industry) - Sungkawaningrum, Fatmawati; Handona, Farhatul; Sariyekti, Eko (Sharia Oikonomia Law Journal, 2024)
The development of the small industrial sector in Indonesia, especially home industry, is important in driving the community's economy, creating jobs and increasing household income. In the context of Islamic economics, entrepreneurship is recommended as part of worship to fulfill life's needs in a halal way. Home industry plays a strategic role in utilizing local raw materials and increasing economic resilience to crises. This research aims to explore the role of the Ijuk Argo Jaya Home Industry in absorbing labor and improving the household economy in Bringin Tegalsari Kedu Hamlet, Temanggung Regency. The scope of this research identifies the role of the Argo Jaya palm fiber home industry in absorbing labor and improving the household economy in the local community. This research method uses a case study with primary data from observation, interviews and documentation, as well as secondary data from relevant literature. Data analysis was carried out through data reduction, data presentation, and drawing conclusions which were verified by triangulation of sources and techniques. The research findings of the Argo Jaya palm fiber home industry provide permanent employment, especially for the elderly and housewives, increasing the flexibility of working hours and adapting to labor needs. This home industry plays an important role in empowering local communities and improving the household economy